Pengembangan Lampu Warna terhadap Perkembangan Kognitif Anak Kelompok A di TK PGRI 1 Bancaran - Nurul Kholidiyah; Dwi Nurhayati Adhani; Siti Fadjryana Fitroh (PG-PAUD Trunojoyo, 2020)
Researchers used a development model Borg Gall. Steps to be taken include the research and data collection, planning, early product development, initial test, revise the initial product, the main field testing and revision of the final product. Research and development is carried out through four stages of a trial that is testing subject matter experts, instructional media expert testing, field trials beginning, and major field trials. The subject of research and development that children in group A or 4-5 years in kindergarten PGRI 1 Bangcaran totaling 21 children. The data collection technique using a questionnaire (questionnaire subject matter experts, instructional media expert questionnaire, and the questionnaire responses of children) and documentation. The results showed that the values obtained from the color light matter experts for86.11% with the title of "high", 76.67% of instructional media expert with the title of "high", the initial field trials 83.9%with the title of "high", and the main field trials 86.9%with the title of "high". Based on the results of research and development has been done can be concluded that the media color lights as stimulationability to recognize the concept of color in group A at TK PGRI 1 Bancaran fit for use